2019
DOI: 10.3390/healthcare7040145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Determinants Affecting Indications for Surgery and Chemotherapy in Recurrent Ovarian Granulosa Cell Tumor

Abstract: Background: Because reports on the management of recurrent granulosa cell tumor have been sparse, a consensus as to which patients should undergo surgical resection and which patients should be considered for chemotherapy has not been established. Methods: A total of 21 tumor recurrences in eight patients with granulosa cell tumor were reviewed. Results: Surgery was performed as the main treatment for 13 recurrences, while chemotherapy was chosen as the main treatment for eight recurrences. Complete tumor rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A research that examined 21 relapsed GCT cases in 8 patients suggested that adjuvant therapy may be of benefit in special higher risk situations, and that prognostic algorithms need to be identified at relapse to individualise treatment approaches and help to decide which cases would benefit from combination regimens 13 . Similar to our experience, they found that the number of tumour lesions, was a predictor of subsequent recurrence even when a total resection had been performed, and encouraged consideration of adjuvant chemotherapy for the sub-cohort of patients with multifocal and diffusely disseminated relapse.…”
Section: Discussionmentioning
confidence: 99%
“…A research that examined 21 relapsed GCT cases in 8 patients suggested that adjuvant therapy may be of benefit in special higher risk situations, and that prognostic algorithms need to be identified at relapse to individualise treatment approaches and help to decide which cases would benefit from combination regimens 13 . Similar to our experience, they found that the number of tumour lesions, was a predictor of subsequent recurrence even when a total resection had been performed, and encouraged consideration of adjuvant chemotherapy for the sub-cohort of patients with multifocal and diffusely disseminated relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen to 23% of GCT ultimately develop recurrent disease and recurrence may be detected many years after the initial treatment, thus prolonged surveillance is necessary 2,4,6,17,21,22 . Shim et al .…”
Section: Recurrent Granulosa Cell Tumormentioning
confidence: 99%
“…Given the recurrence pattern of GCT, CRS seems a reasonable treatment option. The rate of optimal debulking for recurrent GCT has been reported as 81.3% (13 of 16) 6 . In this study, the authors considered a case with recurrence close to porta hepatis and peritoneal carcinomatosis to be inoperable.…”
Section: Cytoreductive Surgerymentioning
confidence: 99%
See 2 more Smart Citations